Pengaruh Perilaku Organisasi Terhadap Kualitas Pelayanan Publik - Hamsah, Ade Irma; Hakim, Lukman; Razak, Rosdianti (Universitas Muhammadiyah Makassar, 2020)
The objective of research is to find out the influence of organization behavior in quality of public services in PDAM Office of Makassar City. The type of the research is quantitative. The sample involved in research are and hundred people for society, and the sample used is simple random sampling. In collecting data, the researcher used observation, questionnaire, and documentation. Data analysis technique used in this research is descriptive statistical analysis,correlation, and simple regression. Based on the correlation and simple regression the result of the research shows that the organization behavior quite influential on the quality of public services. The organization behavior variable have a influence and have a relationship with quality of public service variable.Keywords: Influence, Behavior, Public Services